Teatime at Grosvenor Square : an unofficial cookbook for fans of Bridgerton : 75 sinfully delectable - Clearwater, Dahlia (Skyhorse Publishing, 2021)
" You are cordially invited to dine with society’s finest! From the magnificent macaron towers to the heavenly fruit-topped trifles, the food of Bridgerton steals the show. Teatime at Grosvenor Square brings you 75 tempting recipes inspired by those candy-colored treats and opulent feasts. Now you can create a spread of delicate finger sandwiches, captivating canapés, and bite-sized sweets scrumptious enough to impress Queen Charlotte herself! Plus, you’ll find a few recipes worthy of a Bridgerton family supper."--Amazon.